Cancer and changes in facial appearance: A meta‐ethnography of qualitative studies. Issue 1 (2nd January 2020) - Thompson, Andrew R.; Sewards, Iona; Baker, Sarah R.
Abstract : Introduction: Living with an altered facial appearance as a result of treatment for cancer requires considerable psychological adjustment. As such it is essential that health care professionals understand the lived experience of people affected. This systematic review provides a meta‐ethnography of studies that have explored the experience of changed facial appearance as a result of cancer. Methods: A search of four databases (Web of Science, CINAHL, PsycInfo, and Scopus) took place using terms relating to qualitative research, cancer, and changed facial appearance. Thirteen studies were identified, appraised, and included in the synthesis. The findings and interpretations within the studies were subject to meta‐ethnography procedures so as to elicit novel cross‐cutting themes. Findings: The experience of changed facial appearance after cancer was clustered into three contexts. In the context of the disease, subthemes were the primacy of survival, the changing relationship with the disease, and the impact of the care team on the experience of changed appearance. In the context of the social world, subthemes were positive reactions, negative reactions, and coping strategies. In the context of the self, subthemes were the self under attack, self‐to‐self relating, the self in the world, and rebuilding the self. Conclusions: The findings indicate that health care professionals must conduct holistic assessments, so as to fully recognize and where necessary address the impact upon self. The meta‐ethnography shows that the experience of facial appearance change following cancer is complex and requires awareness of a number of theoretical areas including identity construction, social support, stigmatization, and the specific literature on visible difference. Statement of contribution What is already known on this subject? Changed facial appearance after cancer can cause significant social difficulties and impact on the sense of self. The experience of managing the specific dual challenges of cancer and altered facial appearance is not clearly understood. Recent studies that have focused specifically on the experience of changes in appearance after cancer have been limited in scope and transferability. What does this study add? To our knowledge, this is the first meta‐ethnography to bring together the literature on the impact of altered facial appearance following cancer. Patients may feel unable to talk about appearance with health care professionals because it is seen as a frivolous issue. Clinicians should facilitate open, person‐centred opportunities for patients to discuss the impact of changed appearance and where necessary facilitate access to support.